A naringin-derived bioink enhances the shape fidelity of 3D bioprinting and efficiency of cartilage defect repair. Issue 36 (31st August 2022) - Huang, Yuting; Meng, Xiaolin; Zhou, Zheng; Zhu, Wenxiang; Chen, Xin; He, Yahui; He, Ning; Han, Xiaoxiao; Zhou, Dengming; Duan, Xuanchu; Vadgama, Pankaj M.; Liu, Hairong
Abstract : A NAR derived medical bioink for high shape fidelity 3D bioprinting and cartilage defect repair. MA: methacrylic anhydride, NARMA: methylacryloyl modified NAR, GEL: gelatin, GELMA: methylacryloyl modified GEL. Abstract : 3D bioprinting is a major area of interest in health sciences for customized manufacturing, but lacks specific bioinks to enhance the shape fidelity of 3D bioprinting and efficiency of tissue repair for particular clinical purposes. A naringin derived bioink, which contains 1.5 mM methylacryloyl naringin and 0.15 mM methylacryloyl gelatin, improves the fidelity of 3D bioprinting due to 405 nm light absorption of methylacryloyl naringin. The naringin derived bioink promotes the growth of chondrocytes due to preserving bioactivities of naringin and functions as a medical ingredient from which it has been described as a medical bioink in this study. It facilitates cartilage regeneration by upregulating the transcription of chondrogenesis-related genes like SOX9 and genes against oxidative stress like SOD1 and SOD2 and maintains chondrocytes active resulting from the significantly enhanced COL II / COL I ratio. According to a rabbit cartilage defect model, the proposed naringin derived medical bioink significantly improves the efficiency and quality of cartilage defect repair, suggesting that the bioink is suitable for cartilage defect repair applications and a feasible strategy is provided for the formulation of medical bioinks for specific clinical purposes.